Metrological and operational characteristics of the multichannel vacuum atomic-emission spectrometer for educational and industrial laboratories with a MS-200UN spark generator - Bychkov, Vladimir M.; Didkovsky, Yaroslav I.; Kovalenko, Maksim N.; Minko, Anatoli A.; Pasliadovich, Mikhail R.; Sharashkin, Sergei N.; Yakavets, Vera M. (Journal of the Belarusian State University. Physics, 2019)
This work presents the metrological and operational characteristics of the multichannel vacuum atomic-emission spectrometer for educational and industrial laboratories with a MS-200UN spark generator. The spectrometer uses an original optical scheme consisting of two polychromators: the first polychromator is designed to work in the field of vacuum ultraviolet at the wavelength range from 170 to 290 nm; the second polychromator covers the wavelength range from 290 to 410 nm. The multielement semiconductor photodetectors with remote shielding windows offer fast recording of spectra in the vacuum ultraviolet range for simultaneous evaluation of the concentrations of several chemical elements in the samples under study. It is demonstrated that metrological characteristics of the atomic-emission vacuum spectrometer with a MS-200UN spark generator for educational and industrial laboratories meet the requirements of the normative documents standardizing analysis of metals and alloys. The designed spectrometer may be used in educational process and during routine analyses at laboratories of industrial enterprises and other organizations.